Work-family preferences and employment trajectories of mothers in different welfare state regimes (1994-2012) - García-Faroldi, Livia (My University, 2019)
This study examines the consistency between attitudes towards maternal employment and the actual employment trajectories of partnered mothers in 5 European countries (Great Britain, Germany, Norway, Spain and Czech Republic). These countries represent different welfare regimes and all of them have suffered changes in family policies in last decades. For this purpose, we used data from the ISSP Module ‘Family and Changing Gender Roles’ (1994, 2002 and 2012). We find significant variations in the percentage of mothers who matched what they considered ideal with what they actually did. Women living in the ex-socialist country reported more frequently that they worked more than desired, in contrast to mothers in conservative welfare regimes, who declared that they worked less than desired or did not work at all, even if they wanted to. Mothers in Norway and Great Britain show the greater consistency between attitudes and behaviors. We explore the implications of these results for two confronted theories: Hakim's preference theory and the institutional approach.
Keywords: Madres; Empleo; Madres -- Trabajo; Bienestar social; Congresos y conferencias; Welfare regimes; Maternal employment; International Social Survey Programme; Public attitudes